Deixis Found In Your Place Or Mine Movie Script - vinnaruhitadewi; Indrawati, Ni Luh Ketut Mas; Matradewi, Ni Ketut Widhiarcani (Denpasar Institute, 2025)
Deixis plays a crucial role in pragmatics by helping listeners interpret meaning through contextual cues within an utterance. Despite its importance in effective communication, many language users still struggle to identify and explain deictic expressions accurately. This study addresses that gap by categorizing deixis types and analyzing their referential functions in the movie script Your Place or Mine. Using a qualitative descriptive method, the research employed the film transcript as its primary data. The process involved obtaining the script, repeatedly watching the movie, identifying deictic expressions, and marking them for analysis. The study applies Levinson’s (1983) framework—covering personal, spatial, temporal, social, and discourse deixis—alongside Birner’s (2013) reference theory on anaphora and cataphora. The findings show that all five deixis types appear in the script, with personal deixis occurring most frequently. Overall, the results highlight how deixis enhances communicative clarity and demonstrate the value of reference theory in interpreting deictic expressions in film dialogue.